Using Energy Policies to Shape Local Competitive Advantages - Jakub Grabowski; Jarosław Ropęga; Anna Walecka; Marta Wiśniewska (Energies, 2023)
The aim of this study was to assess urban policies from the point of view of their impact on energy efficiency as a factor enhancing local competitiveness in Poland. To achieve this objective, we carried out an original study. The first step was to conduct a literature review. Next, an attempt was made to present the prevailing state of knowledge regarding the management of the competitiveness of cities and regions, as well as the functioning of energy efficiency in the economy. The development strategies of 18 selected cities serving as provincial capitals or playing other administrative roles at the regional level were also analysed. Importantly, the impact envisaged for municipal authorities to improve energy efficiency largely focuses on investments in the modernisation of public transport infrastructure and renewable energy sources. These investments certainly yield substantial cost savings, which are presented in the article. Nevertheless, it is essential to bear in mind that these are not the sole advantages of increased energy efficiency of local socio-economic systems. The investments also have the potential to enhance the perception of cities, increase the value of municipal real estate, and improve the health of urban residents by reducing emissions into the atmosphere. Still, a clearly discernible link between these arguments and a positive impact of cities’ energy savings on their competitive standing and competitive edge is absent from the analysed city development strategies.